A System Dynamics Modeling and Computer-based Simulation in Forecasting Long-term Sufficiency: A Philippine Chicken Meat Sector Case Study - Espino, M. T. M.; Bellotindos, L. M. (Engineering, Technology & Applied Science Research, 2020)
As the human population continues to grow, the global growth of the livestock sector will continue to rise as well. In the Philippines, the demand for chicken meat is projected to triple by 2050. In this study, the increasing consumption and long-term sufficiency were evaluated with the use of the system dynamics concept. With system modeling and computer-based simulation techniques, the available data on chicken meat supply chain were processed considering that factors behave dynamically. The simulated model facilitated the forecasting of key variables which may drop sufficiency from 87% in 2015 to 60% by 2050 if no proper actions take place in the areas of production and consumption. As a whole, this study developed and demonstrated preliminary system dynamics-based and computer based-approaches in order to understand the chicken meat sector. This showed that a dynamic systems-based paradigm shift in food and agricultural systems analysis can help address operational and strategic issues regarding food security.